2008
DOI: 10.1111/j.1445-5994.2007.01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of stages I and II non‐small‐cell lung cancer in a New Zealand study: divergence from international practice and recommendations

Abstract: Relatively fewer patients received potentially curative treatment in this NZ study than in countries with better survival outcomes and many were not managed within recommended time frames. Management differences increased with increasing age and comorbidity, possibly suggesting more nihilistic attitudes in NZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
5
23
1
Order By: Relevance
“…some comorbid conditions may affect or limit treatment options or decisions). In New Zealand, comorbidity has been found to contribute to ethnic-specific survival disparities for colon cancer [12], the management of stages I and II non-small-cell lung cancer [13], and adverse event status, inpatient death and increased length of stay in selected Auckland hospitals [14]. Internationally comorbidity has also been found to adversely affect survival in patients with a range of conditions, including cervical cancer [15-21].…”
Section: Introductionmentioning
confidence: 99%
“…some comorbid conditions may affect or limit treatment options or decisions). In New Zealand, comorbidity has been found to contribute to ethnic-specific survival disparities for colon cancer [12], the management of stages I and II non-small-cell lung cancer [13], and adverse event status, inpatient death and increased length of stay in selected Auckland hospitals [14]. Internationally comorbidity has also been found to adversely affect survival in patients with a range of conditions, including cervical cancer [15-21].…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies (Cuffe et al, 2012;Girones et al, 2012;Grose, Devereux & Milroy, 2011;Haasbeek et al, 2012;Landrum et al, 2012;Ngeow et al, 2010;Stevens, Stevens, Kolbe, & Cox, 2008;Vinod et al, 2008;Wang et al, 2012) relate to this gap. UK guidelines note that age alone should not exclude a patient from surgery as good outcomes have been reported for some older patients .…”
Section: Gap 4: Older Age and Co-morbidities Influence The Use Of Tmentioning
confidence: 99%
“…UK guidelines note that age alone should not exclude a patient from surgery as good outcomes have been reported for some older patients . The under-utilisation of treatment for the elderly is evident in population-based studies from Australia, the UK, New Zealand, Singapore, Canada, the USA and the Netherlands (Cuffe et al, 2012;Grose et al, 2011;Haasbeek et al, 2012;Landrum et al, 2012;Ngeow et al, 2010;Stevens et al, 2008;Vinod et al, 2008) although gradual improvements during the 2000s are reported. The under-utilisation of treatment for the elderly is evident in population-based studies from Australia, the UK, New Zealand, Singapore, Canada, the USA and the Netherlands (Cuffe et al, 2012;Grose et al, 2011;Haasbeek et al, 2012;Landrum et al, 2012;Ngeow et al, 2010;Stevens et al, 2008;Vinod et al, 2008) although gradual improvements during the 2000s are reported.…”
Section: Gap 4: Older Age and Co-morbidities Influence The Use Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences have increased in recent years, although survival has improved in both countries (Elwood, Aye, & TinTin, ). Much of this disparity is because NZ patients are generally diagnosed at a more advanced stage, as has been shown in studies of, for example, lung (Beatty, Stevens, Stevens, Kolbe, & Cox, ; Stevens, Stevens, Kolbe, & Cox, ), breast (Seneviratne et al., ) and colorectal cancer (Jackson et al., ). Such differences have been seen in other international comparisons and have been influential with regard to re‐organisation of cancer care services, for example, in England and Wales (Richards, , ) and in Denmark (Vedsted & Olesen, ).…”
Section: Introductionmentioning
confidence: 99%